Bakteri Endofit dari daun Katarak (Hippobroma longiflora) : Sumber Potensial Senyawa Antibakteri terhadap Staphylococcus aureus - Arfiandi Arfiandi; Budi Setiawan; Citra Maisy Dian Pratiwi (Journal of Pharmaceutical and Sciences, 2026)
Background: The increasing resistance of Staphylococcus aureus to conventional antibiotics has intensified the search for alternative and more sustainable sources of antibacterial agents. One promising strategy involves the exploration of endophytic bacteria inhabiting medicinal plants, such as Hippobroma longiflora (commonly known as katarak leaves). Objective: This study aimed to isolate endophytic bacteria from Hippobroma longiflora leaves and evaluate their antibacterial activity against Staphylococcus aureus in vitro. Methods: Isolation was carried out through surface sterilization of the leaves using 70% Etanol and 2% Sodium hypochlorite, followed by cultivation on Nutrient Agar. The resulting isolates were subcultured and grown in Nutrient Broth to facilitate the production of secondary metabolites. Antibacterial activity was evaluated using the disc diffusion method, and the inhibition zones were measured. Results: The endophytic bacterial isolates demonstrated antibacterial activity, with an average inhibition zone of 10.15 mm, which was classified as strong. In comparison, chloramphenicol exhibited a significantly larger inhibition zone of 28.52 mm, while the negative control showed no inhibitory effect. Conclusion: These findings suggest that endophytic bacteria isolated from Hippobroma longiflora have potential as a source of antibacterial compounds. However, further optimization and detailed characterization are necessary to enhance their applicability.